On the use of the way-construction with the verb make: A diachronic perspective - González Romero, Luisa (Complutense Journal of English Studies, 2025)
Although the English way-construction is reported to have expanded its semantic domain by recruiting an increasing number of new verbs over the last two centuries, the general verb make remains the most common predicate in all periods since the construction was first attested. Notwithstanding this central role, its use and behaviour has gone almost unnoticed in the abundant literature on the way-construction in favour of other semantically richer verbs. In order to fill this gap, this study is intended to offer a detailed characterization of the way-construction with make by focusing on two core semantic features: the implication of difficult movement or overcoming of barriers that the construction is argued to convey and its ability to express not only concrete movement but also abstract motion. The analysis of a corpus of more than 4,000 occurrences from the last two hundred years provides evidence that cast doubts on the notion of difficult movement being an integral component of the construction and suggests that this meaning is not its prototypical sense anymore. Additionally, and despite the increase in its token productivity in the last decades, the construction does not seem to be more open to the expression of abstract movement.